Uso de resíduos de serragem de mármores do estado do Espírito Santo como corretivo da acidez de solo - Raymundo, Valério (2008)
The great volume of calcareous wastes generated by dimension stone industry and its composition, rich in important elements to promote plant growth, indicate possibilities of utilizing them as amendment of soil acidity. This study aimed to compare the cap